Proanthocyanidins from Ginkgo extract EGb 761® improve bioenergetics and stimulate neurite outgrowth in vitro - Lejri, Imane; Vukalović, Ina; Grimm, Amandine; Eckert, Anne (Frontiers in Pharmacology, 2025)
EGb 761® is a proprietary extract from Ginkgo biloba leaves approved as an herbal medication for the treatment of dementia and its related disorders. Preclinical studies highlight antioxidant, ROS scavenging, mitochondria-stabilizing, and neuroplastic properties as some of the reported pharmacological activities. Efficacy is traditionally ascribed to terpene lactones and flavone glycosides. However, these quantified known active compounds in EGb 761® only cover approximately 30% of the mass balance, and there is the possibility that additional compounds from the residual 70% may enhance the activity of the quantified extract EGb 761®. Proanthocyanidins (PACs) are a quantitatively relevant component in EGb 761®, and some pharmacological activity has been reported for PACs from Ginkgo and other herbal sources. In this study, we focused on the effects of EGb 761® and its isolated PACs on mitochondrial bioenergetics and neuroplasticity in the human neuroblastoma cell line SH-SY5Y. We successfully demonstrated positive effects of EGb 761® and its isolated PACs on several mitochondrial characteristics and neurite outgrowth. As PACs exhibited similar effects compared to the respective extract concentration, they can be considered a pharmacologically relevant component of EGb 761®.